Stomach Content Analysis of Parathelphusa pardus From the Sawah Village, Kampar Regency, Riau Province - Intan Suci Febriani; Windarti '; Efawani ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Parathelphusa pardus is a new freshwater crab species found in the swamp area in the Sawah Village. A study purpose to understand the type of food consumed by the crabs has been conducted in October-November 2016. Crab stomach was removed and its content was analyzed by using a microscope. Type of food present was identified and noted and the Index of Preponderance was calculated. The crabs were captured using a traditional fishing line and traps. Results shown that the stomach of P. pardus contains detritus (64,87%), phytoplankton (28,60%), crustacean remains (5,88%), and algae (0,49%). In each molting status, as well as in male and female crab, the food composition of P. pardus is not different. These crabs may accelerates the degradation of litter particles in the swamp, provide feces as natural food for other small organisms and improve the soil oxygenation through their burrows.Keywords : Parathelphusa pardus, stomach content analyis, Index of Preponderance